Avaliação da expressão de miR-370 e miR-122 e sua participação na regulação do processo de regeneração em prole de camundongos submetidos a cirurgia de hepatectomia parcial : Evaluation of the expression of miR-370 and miR-122 and its participation in the regulation of the process of regeneration in offispring of obese mice submitted to partial hepatectomy surgery - Fontana, Marina Figueiredo, 1992- (2018)
Orientador: Adriana Souza Torsoni